Effect of flipped classroom versus traditional didactic lecture on learning outcomes among medical students: A crossover study. - Sajan Skaria (Student's Journal of Health Research Africa, 2026)
Background The flipped classroom method is a learner-centric approach that encourages active learning. Even though this method has shown promise in medical education, evidence regarding its effectiveness in undergraduate anatomy teaching remains limited. Objective: The study compared the flipped classroom teaching method with traditional lecture-based learning among first-year MBBS students. Materials and methods A crossover study was conducted among 142 first-year MBBS students of both genders at American International Institute of Medical Sciences, Udaipur, Rajasthan. The average age of the participants was 19.1 ± 0.8. Two anatomy topics were taught using a flipped-classroom and traditional lecture method. Performance was assessed using pre- and post-test MCQs, and student perception was evaluated using a structured Likert-scale questionnaire. Data were analysed using t-tests, with p